Evaluation of Inflow Cannulation Site for Implantation of Right‐Sided Rotary Ventricular Assist Device. Issue 8 (29th April 2013) - Gregory, Shaun D.; Pearcy, Mark J.; Fraser, John; Timms, Daniel
Abstract Right heart dysfunction is one of the most serious complications following implantation of a left ventricular assist device, often leading to the requirement for short‐ or long‐term right ventricular assist device (RVAD) support. The inflow cannulation site induces major hemodynamic changes and so there is a need to optimize the site used depending on the patient's condition. Therefore, this study evaluated and compared the hemodynamic influence of right atrial cannulation (RAC) and right ventricular cannulation (RVC) inflow sites. An in vitro variable heart failure mock circulation loop was used to compare RAC and RVC in mild and severe biventricular heart failure (BHF) conditions. In the severe BHF condition, higher ventricular ejection fraction (RAC: 13.6%, RVC: 32.7%) and thus improved heart chamber and RVAD washout were observed with RVC, which suggested this strategy might be preferable for long‐term support (i.e., bridge‐to‐transplant or destination therapy) to reduce the risk of thrombus formation. In the mild BHF condition, higher pulmonary valve flow (RAC: 3.33 L/min, RVC: 1.97 L/min) and lower right ventricular stroke work (RAC: 0.10 W, RVC: 0.13 W) and volumes were recorded with RAC. These results indicate an improved potential for myocardial recovery, thus RAC should be chosen in this condition. This in vitro study suggests that RVAD inflow cannulation site should be chosen on a patient‐specific basis with a view to the support strategy to promote myocardial recovery or reduce the risk of long‐term complications.